ANALISIS RELEVANSI CITY BRANDING KOTA BANDUNG MELALUI PENDEKATAN NILAI INDEKS KEBAHAGIAAN - Rani Sukmadewi; Nurillah Jamil Achmawati Novel (Universitas Padjadjaran, 2020)
This study aims to determine the relevance of Bandung city branding through the happiness index value approach. The research method used is a survey and literature review on six aspects of measuring the effectiveness of city branding, namely presence, place, potential, pulse, people, and pre-requisites. The results of this study indicate that Bandung has become a “Kota Bahagia” that is supported by a happiness index that has continued to increase for several years in a row since 2015. Survey results, studies and analysis of six aspects of measuring the effectiveness of city branding show the branding power of Bandung that is easily recognized and transferred to anyone who lives and visits the city of Bandung. Although some notes to be improved and strengthened as a branding of Bandung such as aspects of Sundanese Culture which experienced a shift due to modernization. In conclusion, the city of Bandung as a “Kota Bahagia” continues to be pursued and improved through the effectiveness of the sustainable city branding program of Bandung. Penelitian ini bertujuan untuk mengetahui relevansi city branding Kota Bandung melalui pendekatan nilai indeks kebahagiaan. Metode penelitian yang digunakan adalah survey dan kajian pustaka terhadap enam aspek pengukuran efektifitas city branding, yaitu presence, place, potential, pulse, people, dan pre-requisites. Hasil penelitian ini menunjukkan Kota Bandung menjadi Kota Bahagia yang didukung oleh indeks kebahagiaan yang terus meningkat selama beberapa tahun berturut-turut sejak tahun 2015. Hasil survey, kajian dan analisis terhadap enam aspek pengukuran efektifitas city branding menunjukkan kekuatan branding Kota Bandung yang mudah dikenali dan ditransfer kepada siapa saja yang tinggal dan berkunjung ke Kota Bandung. Meski beberapa hal menjadi catatan untuk dapat ditingkatkan dan dikuatkan sebagai branding Kota Bandung seperti aspek Budaya Sunda yang mengalami pergeseran akibat modernisasi. Kesimpulannya, Kota Bandung sebagai Kota Bahagia terus diupayakan dan ditingkatkan melalui efektifitas program city branding Kota Bandung secara berkelanjutan.